Returns and volatility of water investments - Rajibur Reza; Gurudeo Anand Tularam; Bin Li (Cogent Economics & Finance, 2018)
This study analyzes the stock returns and volatility of the global water industry in different (full, pre-GFC, GFC and post-GFC) periods. The study estimates ARMA (1, 1)-GARCH (1, 1) and EGARCH (1, 1) models on the World Water index (WOWAX), S-Network Global Water Index (S-Net), S&P Global Water Index (S&P), and MSCI ACWI Water Utilities Index (MSCI ACWI), the Asia, Europe, Latin America and US water markets, Pictet Global Water Fund (Pictet), and KBC Eco Water Fund (KBC Eco) for the period 2004-2014. In this study, the EGARCH (1, 1) model results suggest the existence of persistence of volatility from four water indices, four water markets and two water funds in different periods and asymmetric volatil- ity (leverage) for Asia and US, S-Net and Pictet in full, pre-GFC and GFC periods and for WOWAX in GFC and post-GFC periods. The WOWAX is not highly correlated with water markets and water funds, which suggests that it may provide a possible op- portunity for portfolio diversification in different periods.
Keywords: 330; water investments; water indices; water markets; volatility